Creative and Productive Teaching: Instructional Model for Developing Learners in the 21st Century - Sirichokchaitrakool, Sirisukr (Ratchaphruek Journal, 2021)
The key to develop learners in the 21st century is the teaching methods development and appropriate teaching and learning in the era, including the creation of knowledge adapted to the changing world society. This academic article aimed to present the concept of the Creative Teaching and Productive Model (CRP Model) which consisted of: 1) Crystallized teaching (Crystal-based Instructional Model); 2) Teaching by research method (Research-based Instructional Model) l; and 3) Teaching productivity.(Productivity-based Instructional Model). Highlight of the CRP Model is the usage of a teaching process that allows students to expand their ideas, practice and self-directed learning based-on the concept of constructivism theory. They can produce the creative works according to their aptitudes and interests. This interesting teaching style will be developed the 21st century learners’ characteristics, and will be a major social capital in driving the country’s development.